Status Gizi Pasien Tuberkulosis Paru pada Anak Sebelum dan Sesudah Terapi Obat Anti Tuberkulosis (OAT) - Aufa Salsabila Surahman; Nanan Sekarwana; Harvi Puspa Wardani (Bandung Conference Series: Medical Science, 2023)
Abstract. Nutritional status in pediatric tuberculosis (TB) patients plays an important role in the course of TB disease. After being given appropriate TB therapy, the infection process begins to decrease and there is an increase in the formation of fatty acids and a decrease in the process of lipolysis in the tissues. The purpose of this study was to analyze the differences in the nutritional status of pulmonary tuberculosis patients in children before and after therapy at the Children's Polyclinic at Al-Islam Hospital Bandung in 2019 – 2020. The research subjects were children with pulmonary TB aged 0 – 4 years who had completed therapy and were selected using a purposive sampling technique. This study used an analytic observational method with a cross-sectional design. Data on body weight (BB) and age were obtained from medical records and grouped into three categories of nutritional status. The number of samples in this study was 67 children with pulmonary TB. The results of the study showed that before TB therapy, 26 (39%) people had poor nutritional status, 40 (60%) people had normal nutritional status, and only one (1%) person had a risk of being overweight. After therapy, 13 (19%) people had underweight nutritional status, 50 (75%) normal weight nutritional status, and four (6%) people had a risk of being overweight. The results showed that there were significant differences in the nutritional status of children before and after TB therapy (p 0.001; <0.05). In conclusion, there are significant differences regarding the nutritional status of pulmonary tuberculosis patients in children before and after therapy. Keywords: Pediatric tuberculosis, nutritional status, therapy. Abstrak. Status gizi pada pasien tuberkulosis (TB) anak berperan penting dalam perjalanan penyakit TB. Setelah diberikan terapi TB yang tepat maka proses infeksi mulai berkurang dan terjadi peningkatan pembentukkan asam lemak dan penurunan proses lipolisis di jaringan. Tujuan penelitian ini adalah menganalisis perbedaan status gizi pasien tuberkulosis paru pada anak sebelum dan sesudah terapi di Poli Anak Rumah Sakit Al – Islam Bandung tahun 2019 – 2020. Subjek penelitian adalah anak penderita TB paru berusia 0 – 4 tahun yang telah menyelesaikan terapi dan dipilih menggunakan teknik purposive sampling. Penelitian ini menggunakan metode observasional analitik dengan desain cross sectional. Data berat badan (BB) dan usia diperoleh dari rekam medis dan dikelompokkan menjadi tiga kategori status gizi. Jumlah sampel penelitian ini adalah 67 penderita TB paru anak. Hasil penelitian didapatkan bahwa sebelum dilakukan terapi TB 26 (39%) orang memiliki status gizi BB kurang, 40 (60%) orang berstatus gizi BB normal, dan hanya satu (1%) orang yang memiliki risiko BB lebih. Sesudah dilakukan terapi sebanyak 13 (19%) orang memiliki status gizi BB kurang, sebanyak 50 (75%) berstatus gizi BB normal, dan empat (6%) orang memiliki risiko BB lebih. Hasil penelitian menunjukkan terdapat perbedaan yang signifikan pada status gizi anak sebelum dan sesudah dilakukan terapi TB (p 0,001; <0,05). Simpulan, terdapat perbedaan yang signifikan terkait status gizi pasien tuberkulosis paru pada anak sebelum dan sesudah terapi. Kata Kunci: Tuberkulosis anak, status gizi, terapi.